Ixodicide activity of Eysenhardtia polystachya against Rhipicephalus (Boophilus) microplus. Issue 4 (1st April 2015) - Gutierrez, L.; Sumano, H.; Rivero, F.; Alcala-Canto, Y.
Abstract: The objective of this study was to evaluate the acaricidal effect of 2 compounds extracted from Eysenhardtia polystachya in vitro, namely coatlines and matlalines. Each extract was obtained by aqueous extraction in a nitrogen atmosphere. Engorged adult females of an amitraz-resistant strain of Rhipicephalus ( Boophilus ) microplus were used to produce larvae and to carry out the adult immersion test (AIT), while larvae were assayed using the larval packet test (LPT). After exposure to coatlines or matlalines, the mortality of larvae and engorged females, as well as the reproductive parameters of adult ticks were assessed. Coatlines were not lethal against larvae and did not decrease reproductive parameters. Conversely, matlalines showed a 90 to 100% efficacy against adults and larvae at all concentrations tested and a reduction of 76.41 to 80.64% oviposition and a 48.02 to 54.86% reduction in egg hatchability. Therefore, the acaricidal activity of matlalines was more efficient. Further studies are required to elucidate both the mode of action of matlalines as well the structure-activity relationships responsible for the observed differential efficacy between these 2 related isoflavans against the cattle tick.